Exploring the Cultural Relevance and Pedagogical Practices of Mother Fixation in Reference to Sons and Lovers - Prof. Dr. Shumaila Mazhar; Dr. Najia Almas (Journal of Peace, Development and Communication, 2023)
Sons and Lovers has been among the most significant works of D.H. Lawrence which is being taught in many universities of Pakistan for several years. As a piece of art, undeniably, this novel conveys some moral values and an exact picture of life, but the dominant theme about the phenomenon of Mother Fixation exercises some adverse impact on students’ perception for its being a taboo in our society. Thus, the present study aims at exploring the effective pedagogical practices of the Theme of Mother Fixation to Pakistani students through investigating the attitudes and opinions of teachers. It has adopted phenomenology as a research paradigm. Data was collected from two universities in Quetta city. The study examined some of the obstacles that teachers face in literature class, while dealing with this theme as well as how they tend to overcome these hurdles. There is some indication from the data that majority of the respondents expressed feelings of embarrassment and hesitation while discussing the Theme of Mother Fixation, especially in the presence of the opposite sex and preferred to avoid the sensitive aspect of incestuous relationships in the novel. The result has shown that the Theme of Mother Fixation, if handled properly while observing the ethical limitations of Pakistani society, would not harm the perception of the students about their family values. In addition to this, teachers cited valid concerns about giving a detailed and comprehensive analysis of the psychological aspect of the theme, taking into consideration the cultural reservations of Pakistani society.